Esh hada?! (ano ito?!) a study on how Filipinos in Jeddah, Saudi Arabia perceived the news about the Philippines shown on TV Patrol World during Presidential Decree 1017 - Labayen, Sophia Rae R. 1985-
"Filipinos abroad have always been portrayed as the son, the daughter, the father or the mother who left the Philippines behind to better provide for their families. Because of this martyr-like portrayal of scarifice, they have become known as the New Heroes of the Philippines (mga Bagong Bayani), raking in remittances year after year, which not only help their families but also the economy of the Philippines. Because they are away, there is that constant longing, if not to be home, then at least to get a glimpse of home and this is provided through the Filipino cable-provider, The Filipino Channel. Through TFC, the Filipino abroad has access to the latest events in the Philippines, particularly shown on the news program, TV Patrol world, as the news supposedly shows the audience factual details as to what is really happening as opposed to situational comedies and variety shows that provided entertainment. In this study, results show that the Filipino audience abroad has become critical to the point of not wholly believing anymore in the news about the Philippines shown on TV Patrol World, particularly during PD 1017. Because of the manner that TV Patrol presents it news: the choice of issues and angle to focus on, the long duration of a particular issues on the airwaves and, according to the respondents of the study, the evident slant in TV Patrol World's reporters, the Filipino audience abroad, though eager to hear news about the Philippines, has grown tired of hearing only negative stories about the homeland as this dampens their morale and hopw for the country. Also of concern to the Filipino audience abroad is the image of the Philippine to foreigners since these foreigners also have access to TFC. The study shows that the respondents feel it is their moral obligation, as they are part of that country, to continually defend the Philippines by negating all the negative publicity shown in the news. As soldiers in the battlefield need uplifting of their morale to function better, so do the Filipinos abroad. These new heroes' call is for a more responsible, balanced and nationalist media that will encourage a common nationalist sentiment and that will promote national development."